RESPON POTENSIAL MEMBRAN SEL TELUR IKAN NILA (Oreochromis niloticus) AKIBAT TERKONTAMINASI TIMBAL (Pb) - Bobu, Fetronela Rambu (EduFisika: Jurnal Pendidikan Fisika, 2022)
Tilapia egg cells give different responses when given variations in the concentration of lead (Pb) pollutant. This study used a microelectrode connected to a picoscope to measure the potential value of tilapia egg cell membrane. The results of the study show that tilapia egg cells contaminated with Pb will cause changes in the cell membrane potential. The concentration of Pb given consisted of six variations, namely 0.02 ppm; 0.03ppm; 0.05ppm; 0.1 ppm ; 0.5ppm; and 1ppm. Tilapia eggs exposed to Pb with the highest concentration of 1ppm caused the cells to experience a significant decrease in the membrane potential of -7.77 mV. At this point, tilapia egg cells experience a decrease in membrane potential until they experience cell death.